Intramolecular Charge‐Transfer Dynamics in Benzodifuran‐Based Triads. Issue 9 (17th August 2021) - Keller, Stephan; Hankache, Jihane; Yushchenko, Oleksandr; Lawson Daku, Latévi Max; Sun, Qinchao; Ding, Jie; Decurtins, Silvio; Vauthey, Eric; Häner, Robert; Hauser, Andreas; Liu, Shi‐Xia
Abstract: A facile and efficient approach for the synthesis of new conjugated donor‐π‐acceptor (D‐π‐A) chromophores has been developed, in which benzodifuran (BDF) and/or triphenyl amine (TPA) units are the donor moieties, linked by ethylenic bridges to electron‐deficient anthraquinone (AQ) and 11, 11, 12, 12‐tetracyano‐9, 10‐anthraquinodimethane (TCAQ) as the acceptor moieties. The resultant triads either with a symmetric A–D–A or an asymmetric D′–D–A structure show intense absorption bands in the visible spectral region due to efficient intramolecular charge transfer (ICT) from the HOMO localized on the BDF core to the LUMO localized on the AQ or the TCAQ unit. Electronic interactions between these redox‐active components were studied by a combination of cyclic voltammetry, spectroelectrochemistry, UV‐visible and ultrafast transient absorption spectroscopy. Analysis of the femtosecond excited‐state dynamics reveal that all triads undergo a rapid charge recombination process which occurs within a few picoseconds, indicating that ethylenic linkers can facilitate electron delocalization among BDF and AQ/TCAQ units and thus impart effective electronic interactions between them. Abstract :